Analisis Pengaruh Pemungutan Pajak Parkir, Pajak Hotel dan Pajak Penerangan Jalan Terhadap Pendapatan Asli Daerah Kabupaten Sukoharjo - Meysha Puspa Sari; LMS Kristiyanti; Suhesti Ningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of Parking Tax, Hotel Tax, and Street Lighting Tax collection on the Regional Original Revenue (PAD) of Sukoharjo Regency. The research uses a quantitative method with a multiple linear regression approach. The data analyzed are secondary data from the 2019–2023 period obtained from the Regional Financial and Asset Management Agency (BPKAD) of Sukoharjo Regency. The results show that Hotel Tax and Street Lighting Tax have a significant effect on PAD, while Parking Tax does not have a significant effect. These findings indicate the need to optimize Parking Tax management and improve collection strategies for Hotel Tax and Street Lighting Tax to enhance regional fiscal independence.